Effect of Democratic Leadership Styles on Corporate Performance - Hikmat, Hikmatullah; Ghorbandi, Nangyalai (Journal for Research in Applied Sciences and Biotechnology, 2024)
This study investigated the impact of Democratic Leadership Style on employee business development within the private sector. The primary objective is to assess how Democratic Leadership Style influences organizational behavior. This was further divided into two specific objectives: (1) to explore the influence of Democratic Leadership Style on organizational behavior, and (2) to examine the relationship between Democratic Leadership Style and organizational behavior. The main research question is: "What is the effect of Democratic Leadership Style on organizational behavior?" Sub-questions include: "What is the influence of Democratic Leadership Style on organizational behavior?" and "What is the relationship between Democratic Leadership Style and organizational behavior?" The hypothesis posits that Democratic Leadership Style has a positive effect on organizational behavior, with sub-hypotheses suggesting that this style enhances organizational behavior and establishes a positive relationship between the leadership style and organizational behavior. Data was collected through both primary and secondary methods, including 30 distributed questionnaires and information from relevant books, websites, journals, articles, and magazines. Findings indicate that Democratic Leadership Style positively affects employee business development, skills enhancement, productivity, and morale. This style also allows employees to contribute to daily operations, supports work-life balance, and improves employee retention rates.